Effect of Feed Intake on Water Consumption in Horses: Relevance to Maintenance Fluid Therapy - Freeman, David E. (Frontiers in Veterinary Science, 2021)
Maintenance fluid therapy is challenging in horses that cannot drink or are denied feed and water because of concerns about gastrointestinal tract function and patency. Intravenous fluid delivery to meet water needs based on current recommendations for maintenance requirements were obtained in fed horses and therefore might not apply to horses that are not being fed. This is a critical flaw because of the interdependence between intestinal tract water and extracellular water to support digestion while preserving water balance, a concept explained by the enterosystemic cycle. Because horses drink less when they are not eating and hence have lower water needs than fed horses, maintenance water requirements need to be adjusted accordingly. This article reviews this topic and identifies benefits of adjusting maintenance fluid therapy to meet lower demands from gastrointestinal function, such as reduced volumes, lower cost, avoidance of overhydration.